Effectiveness of Implementation of Household Waste Management Policy in North Jakarta - Fadlillah, Faqri; Sofilda, Eleonora; Sumiyarti, Sumiyarti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Waste is something that cannot be avoided in a problem in an area. The increase in population in a city causes waste to increase according to people's consumption. The waste that often arises is household waste, where according to data from the National Waste Management Information System, 60% of waste is generated from households. This research aims to find out to what extent a policy on Household Waste Management in North Jakarta produces results in terms of institutional role, interpretation of a policy, implementation of the policy, and impact of the policy. The policies created can analyze and examine the role of the institution, the interpretation of the policy, its implementation, and its impact on society. This policy only exists in DKI Jakarta to regulate the amount of waste generated when it is known that the Bantar Gebang TPST is already at overload capacity. Therefore, the author conducted research using qualitative methods with several informants in North Jakarta. The informants used by the authors are residents in the North Jakarta area, 22 Operators and Regulators or policymakers, with 3 people working in the Government who are responsible for waste management. This qualitative method of research uses Nvivo software in data processing to obtain results that follow the purpose of writing. Based on Nvivo's results on data processing, it was found that institutional factors and policy interpretation would have an impact on the performance of implementing programs related to regulatory socialization. In the socialization of regulations, it was found that there were inconsistencies in the socialization and a lack of clarity regarding policy implementation.